Cechy klientów pomocy społecznej w opiniach studentów i pracowników socjalnych - komunikat z badań = Clients of social assistance services perceived by students and social workers - research results - Lipowicz, Elżbieta; Łuczak, Aleksandra (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to present the results of the research on the image of social assistance services clients perceived by students and social workers. A realistic, free of bias image of a supported person seems to be an essential condition that must be met by anyone who wants to help other people. Clients of social assistance services usually come from communities exposed in a particular way to discrimination and negative schematization of their image.
Keywords: pomoc społeczna; alkoholizm; narkomania; bezdomność; chorzy psychicznie; studenci; pracownicy socjalni